Prose poetry portfolio - Bonny Cassidy (2021)
Research Background - This portfolio presents prose poems on themes of voice. ‘Pariah’ and ‘The race’ stage dramatic monologues of outrage and disenfranchisement in Australia. These commissions developed directly from my co-editing of Australian Contemporary Feminist Poetry (2017) and my contribution to Reading Victoria (2016). ‘Mandala for Erica McGilchrist’ and ‘The Star’ are collaborations with visual art and an artist to narrate creative process. These works build on my established use of ekphrasis method in Chatelaine (2017) and my scholarly and creative work on non-Indigenous representation. Research Contribution - This portfolio is in dialogue with prose poetry by John Kinsella and Evelyn Araluen. It uses voice and structure to demonstrate that poetry is constituted by affects of tone and abstraction, not shape. The portfolio contrasts neutral tone (‘Pariah’, ‘The Star’) with personal reflection ‘Mandala’), and emotiveness (‘The race’) with observation (‘Mandala’). ‘Mandala’ and The Star’ experiment with what constitutes ekphrasis: through archives ‘Mandala’ responds to the career of artist Erica McGilchrist; while ‘The Star’ is a process-based collaboration with painter Catherine Cassidy through shared subject matter and sources. Research Significance - Through the Melbourne City of Literature’s Poet Laureates project, ‘Pariah’ reached a national mailing list and will be republished in book form (2021). ‘The race’ appeared in a print anthology, Borderless, the first collection of contemporary Australasian feminist poetry to draw on First Nations, diasporic and Pacifica voices. ‘Mandala’ appears in an edited book for Heide Museum of Modern Art and its art audiences. ‘The Star’, globally and permanently accessible through Australia’s leading poetry publication, Cordite Poetry Review will reach cross-disciplinary attention through its presentation as a visual art collaboration.